Diagnostic performance of the aortic dissection detection risk score in patients with suspected acute aortic dissection. Issue 4 (1st December 2014) - Nazerian, Peiman; Giachino, Francesca; Vanni, Simone; Veglio, Maria G; Castelli, Matteo; Lison, Davide; Bitossi, Luca; Moiraghi, Corrado; Grifoni, Stefano; Morello, Fulvio
Abstract: Aims: The aortic dissection detection (ADD) risk score has been proposed by guidelines to standardise the approach to patients with suspected acute aortic dissection (AD). However, the ADD risk score has not been validated so far. Methods and results: Patients with suspected AD from two clinical centres were prospectively enrolled in a registry from 2008 to 2012. The ADD risk score was calculated retrospectively by review of medical charts, according to the number of risk categories where patients met criteria. Of 1328 patients, 291 (21.9%) were diagnosed with AD. The ADD risk score was=0 in 439 (33.1%) patients, =1 in 646 (48.6%) patients and >1 in 243 (18.3%) patients. The incidence of AD was 5.9%, 27.3% and 39.1% respectively in patient groups identified by ADD risk score=0, =1 and >1. ADD risk score>0 had a sensitivity of 91.1% (95% confidence interval (CI) 87.2–94.1%) and a specificity of 39.8% (95% CI 36.8–42.9%) for the diagnosis of AD, while ADD risk score>1 had a sensitivity of 32.7% (95% CI 27.3–38.4%) and a specificity of 85.7% (95% CI 83.5–87.8%). Among patients with ADD risk score=0, mediastinum widening on chest X-ray had a sensitivity of 16.7% (95% CI 3.6-41.4%) and a specificity of 86.3% (95% CI 81.9–90.0%). Conclusion: The ADD risk score stratifies patients for the risk of AD. ADD risk score>0 is highly sensitive and poorly specific for the diagnosis in AD. The presence of ADD risk score=0 per se does not accurately exclude AD. In patients with ADD risk score=0, chest X-ray provides limited diagnostic information.